Frequency of Endometrial Carcinoma in Patients with Postmenopausal Bleeding - NUDRAT SOHAIL, RASHIDA SULTANA (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To determine the frequency of endometrial carcinoma in patients with postmenopausal bleeding and to compare the clinico-demographic features of cases with and without carcinoma. Study design: Descriptive study Setting: Department of Obstetrics and Gynecology, Lahore General Hospital affiliated with Postgraduate Medial Institute, from 14th April 2007 to 13th April 2008. Materials and methods: Sample: 100 patients of postmenopausal bleeding were included. Data was collected from history, examination, investigations and other relevant details of selected cases by using proforma questionnaire. Statistical analysis was done using software SPSS version 10. Results: In present study, 7% cases were diagnosed as endometrial carcinoma on histopathology. All were endometrial adenocarcinoma. Most common cause of postmenopausal bleeding was atrophic endometrium (47% of cases) followed by endometrial hyperplasia, endometritis, endometrial and cervical polyps, cervical carcinoma and sub mucous fibroid, present in 19%, 13%, 8%, 4% and 2% respectively. Mean age of patients with endometrial carcinoma was 69.28± 6.72 years and mean age of menopause was 53.14±3.76 years. Risk factors studied in patients with endometrial carcinoma, 15% had menopause after 55 years of age, 29% were nullipara, 43% patients were hypertensive, 29% were diabetic and 15% of patients had BMI more than 30Kg/m2. Conclusion: Study suggests that although the major causes of postmenopausal bleeding were found to be benign, the frequency of malignancy is still considerably high in women with postmenopausal bleeding in our population. This justifies the need for a thorough assessment and endometrial sampling in all cases of postmenopausal bleeding to decrease the morbidity and mortality associated with endometrial carcinoma.